The Use of Smartphone Assisted Picture Word Inductive Models to Improve Basic Literacy - Asep Deni Gustiana; Rahman Rahman; Tatat Hartati; Nana Supriatna (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
Basic literacy is highly needed to ease students’ understanding of a concept. Therefore, it is necessary to deliver an innovative teaching approach to enhance students’ basic literacy. This study aims to investigate the use of picture word inductive models with the help of smartphones to increase the basic literacy of elementary school students in grade one. This study employed a quantitative approach with quasi experimental methods a pretest-posttest control group design. The population of this study was grade one from elementary school in Bandung City. The sample of this study was two classes (experimental and control) from each school which were selected randomly. The number of samples was 113 consisting of 57 students in the experimental class and 56 people in the control class. To collect data, we used a basic literacy test and analyzed it by using a t-test. This study shows that the use of picture word inductive models with the help of a smartphone can improve basic literacy. The findings of this study are that picture word inductive models with the help of smartphones can facilitate students who have different reading and writing abilities.